Six family genes-structure and function as transcription factors and their roles in development. - Kawakami, K.; Sato, S.; Ozaki, H.; Ikeda, K. (BioEssays, 2000)
The members of the Six gene family were identified as homologues of Drosophila sine oculis which is essential for compound-eye formation. The Six proteins are characterized by the Six domain and the Six-type homeodomain, both of which are essential for specific DNA binding and for cooperative interactions with Eya proteins. Mammals possess six Six genes which can be subdivided into three subclasses, and mutations of Six genes have been identified in human genetic disorders. Characterization of Six genes from various animal phyla revealed the antiquity of this gene family and roles of its members in several different developmental contexts. Some members retain conserved roles as components of the Pax-Six-Eya-Dach regulatory network, which may have been established in the common ancestor of all bilaterians as a toolbox controlling cell proliferation and cell movement during embryogenesis. Gene duplications and cis-regulatory changes may have provided a basis for diverse functions of Six genes in different animal lineages.